Preparation of phosphines through C–P bond formation - Wauters, Iris; Debrouwer, Wouter; Stevens, Christian V. (Beilstein Journal of Organic Chemistry, 2014)
Phosphines are an important class of ligands in the field of metal-catalysis. This has spurred the development of new routes toward functionalized phosphines. Some of the most important C–P bond formation strategies were reviewed and organized according to the hybridization of carbon in the newly formed C–P bond.
Keywords: cross-coupling; enantioselectivity; hydrophosphination; organophosphorus chemistry; phosphines; phosphine-boranes; substitution reactions; trivalent phosphorus